Physical actions and work-rest time in women's beach volleyball - Palao, J. M.; Lopez-Martinez, A. B.; Valades, D.; Ortega, E. (International Journal of Performance Analysis in Sport, 2015)
The purpose of this study was to assess the ball contacts, jumps, hits, work time, and rest time for women's beach volleyball players in relation to their in-game role. The sample of this study was composed of 2,708 rallies played by 48 female beach volleyball players, which corresponded to 69 sets of the 2008 Olympic Games. The variables recorded were: ball contacts, jumps, hits, work time, rest time, and player's role (defense specialist, blocker, or no specialization). A significantly higher number of jumps were performed by blockers. No differences were found in the number of contacts or hits. The work : rest ratio was 1 : 5. This paper discusses how the data can be used to create game-like situations in practices regarding physical demands in women's beach volleyball.